Gamifying software engineering subject to enhance the quality of knowledge - Aldalur, Iñigo (Software, practice & experience, 2024)
Gamification has been widely used in education in recent years. Gamification has been proven to be a useful tool for students, as it motivates them and helps them to learn. The lack of motivation on the part of the students and their poor perception of the importance of software engineering has led to the definition of SESGA. This game has been designed and carried out on third year students of the computer science degree. SESGA has been designed for students to improve their knowledge of static code analysis, unit testing and Git. A software engineering project was carried out in groups, in which each of the students had to perform common software development tasks. The evaluation has measured the accomplishment, challenge, competence, guidance, immersion, playfulness and social involvement of SESGA obtaining remarkable results. It has also shown that SESGA has allowed students to have better academic results and the number of failures has decreased.